Targeting senescent cells improves functional recovery after spinal cord injury - Paramos-de-Carvalho, Diogo (2021)
Funding Information: We are grateful to A. Nascimento, A. Temudo, and J. Rino from the Bioimaging Unit for all of their precious advice. We thank the support given by the Fish and Rodent Facilities and the Histology and Comparative Pathology Laboratory, A. Ribeiro and C. de Sena-Tomás for critical reading of the manuscript, and M. Rebocho-da-Costa for help with the graphical abstract. D.P.d.C. was supported by a FCT PhD fellowship ( PD/BD/105770/2014 ). I.M. was supported by a FCT post-doctoral fellowship ( SFRH/BPD/118051/2016 ). A.M.C. was supported by a FCT fellowship ( PTDC/BOM-MED/3295/2014 ). A.F.D. was supported by CONGENTO LISBOA-01-0145-FEDER-022170 , co-financed by FCT (Portugal) and Lisboa2020 , under the PORTUGAL2020 agreement ( European Regional Development Fund ). D.N.-S. was supported by a FCT PhD fellowship ( SFRH/BD/138636/2018 ). D.C. was supported by a FCT PhD fellowship ( PD/BD/114179/2016 ). L.S. was supported by a FCT IF contract. The project leading to these results has received funding from a FCT grant ( PTDC/MED-NEU/30428/2017 ) and “la Caixa” Banking Foundation and FCT , I.P., under project code HR18-00187 . Publisher Copyright: © 2021 The Author(s) Copyright: Copyright 2021 Elsevier B.V., All rights reserved.